LITERATURE REVIEW ON THE IMPLEMENTATION OF AI AND AUTOMATION IN THE PUBLIC AND PRIVATE SECTORS - Loso Judijanto (Adisam Publisher, 2025)
The implementation of artificial intelligence (AI) and automation in the public and private sectors, highlighting the benefits as well as the challenges it faces. Studies show that the implementation of AI and automation can improve operational efficiency, accuracy, and personalisation of services in various sectors. In the public sector, these technologies help speed up administrative processes, predict community needs, and optimise resources. On the other hand, the private sector is adopting AI to improve productivity, design personalised customer experiences, and support business decisions with in-depth data analysis. However, the study also identified significant challenges, including limitations in technology adoption, gaps in access and expertise, and ethical and privacy issues. Addressing these challenges requires collaboration between stakeholders to develop policies that support workforce retraining, data regulation, and ethical frameworks. With the right approach, AI and automation have the potential to have a broad and sustainable positive impact on social and economic well-being in both the public and private sectors.